Fracture network analysis and 3D structural modeling of Jurassic outcrop in Nizampur Basin, Western Himalayas; implications for reservoir behavior and hydrocarbon mobility - Waqar Ahmad; Syed Ali Turab; Shahab Aman e Room; Aamir Khan; Nasar Khan; Saad Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Field portable Cr2O3 nanozyme based paper sensors for on-site screening of arsenic and cadmium in quality control of herbal products - Fatima Yaseen; Muhammad Faizan; Ali Turab Jafry; Awn Muhammad; Akhtar Hayat; Huma Ajab (Food Bioscience, 2026)

Mineral chemistry and alteration characteristics of sulfide-bearing metavolcanics in the Thalle area, Kohistan–Ladakh Arc: insights into magmatic-hydrothermal fluid evolution - Muhammad Farhan; Tehseen Zafar; Mohammad Arif; Chun-Feng Li; Zahid Hussain; Zaheen Ullah; Syed Wajid Hanif Bukhari; Uzair Siddique; Syed Ali Turab; Mubasir Ali (Geosciences Journal, 2026)

Integrated ARTP mutagenesis with malonate selection rewires CO2 fixation and TCA-redox metabolism for selective MUFA-rich lipid production in Chlorella sorokiniana - Hongwei Li; Xin Sun; Xiaoxiao Sun; Ali Turab; Ali Ishtiaq Muhammad; Binchen Mao (Chemical Engineering Journal, 2026)

Mixed-gas ARTP mutagenesis Decodes the Argon-, Air-, and hybrid Plasma-Specific regulation of Biomass-Lipid-Carbon trade-offs in Chlorella sorokiniana - Hongwei Li; Xin Sun; Lei Ye; Naima Batool; Ali Turab (Bioresource Technology, 2026)

Advancements in a comprehensive framework for microalgal lipid production: ARTP mutation, cultivation optimization and sustainable extraction - Ali Turab; Xin Sun; Ahsan Elahi; Naima Batool; Irfan Khan; Pengfei Li; Hongwei Li (Biomass and Bioenergy, 2026)

Functionalized montmorillonite clay with histidine for phosphate capture and recovery from wastewater sludge: Sustainable application as fertilizer to improve soil properties - Mehr Un Nisa; Asim Yaqub; Tayyab Iqbal; Ali Turab Jafry; Huma Ajab (Applied Clay Science, 2026)

Deep neural networks and stochastic methods for cognitive modeling of rat behavioral dynamics in $$\mathbb {T}$$-mazes - Ali Turab; Josué-Antonio Nescolarde-Selva; Farhan Ullah; Andrés Montoyo; Cicik Alfiniyah; Wutiphol Sintunavarat; Doaa Rizk; Shujaat Ali Zaidi (Cognitive Neurodynamics, 2025)
Modeling animal decision-making requires mathematical rigor and computational analysis to capture underlying cognitive mechanisms. This study presents a cognitive model for rat decision-making behavior in $$\mathbb {T}$$ T -mazes by combining stochastic methods with deep neural architectures. The model adapts Wyckoff’s stochastic framework, originally grounded in Bush’s discrimination learning theory, to describe probabilistic transitions between directional choices under reinforcement contingencies. The existence and uniqueness of solutions are demonstrated via fixed-point theorems, ensuring the formulation is well-posed. The asymptotic properties of the system are examined under boundary conditions to understand the convergence behavior of decision probabilities across trials. Empirical validation is performed using Monte Carlo simulations to compare expected trajectories with the model’s predictive output. The dataset comprises spatial trajectory recordings of rats navigating toward food rewards under controlled experimental protocols. Trajectories are preprocessed through statistical filtering, augmented to address data imbalance, and embedded using t-SNE to visualize separability across behavioral states. A hybrid convolutional-recurrent neural network (CNN-LSTM) is trained on these representations and achieves a classification accuracy of 82.24%, outperforming conventional machine learning models, including support vector machines and random forests. In addition to discrete choice prediction, the network reconstructs continuous paths, enabling full behavioral sequence modeling from partial observations. The integration of stochastic dynamics and deep learning develops a computational basis for analyzing spatial decision-making in animal behavior. The proposed approach contributes to computational models of cognition by linking observable behavior to internal processes in navigational tasks.

Toward cleaner combustion: spray, performance, and emission improvement of castor biodiesel with MoS2 and ABE additives - Muteeb ul Haq; Ali Turab Jafry; Wajahat Ullah Khan; Huma Ajab; Zabdur Rehman; Arslan Ahmad; Taqi Ahmad Cheema; Naseem Abbas (Clean Technologies and Environmental Policy, 2025)

Gas source-dependent reactive oxygen species dynamics and transcriptional reprogramming drive lipid hyperaccumulation in plasma-mutagenized Desmodesmus sp. - Hongwei Li; Xin Sun; Haocheng Li; Yue Xie; Naima Batool; Ali Turab (Journal of Environmental Chemical Engineering, 2025)

Upregulation of photosynthesis and TAG biosynthesis genes enhanced lipid production in ARTP-mutated Scenedesmus sp. via multi-omics analysis - Ali Turab; Xin Sun; Ahsan Elahi; Naima Batool; Hongwei Li; Xiao Xiao Sun (Journal of Environmental Chemical Engineering, 2025)

Fracture analysis and reservoir potential of Jurassic-Paleocene rocks exposed in lower Orakzai area, Lesser Himalayas, Pakistan - Wasif Ullah; Syed Ali Turab; Muhammad Awais Aziz; Nasar Khan (Carbonates and Evaporites, 2025)

Transcriptomics and metabonomics reveal molecular mechanisms promoting lipid production in Haematococcus pluvialis co-mutated by atmospheric and room temperature plasma with ethanol - Ali Turab; Xin Sun; Yihua Ma; Ahsan Elahi; Pengfei Li; Yasir Majeed; Youreng Sun (Bioresource Technology, 2025)

An electrochemical sensing potential of cobalt oxide nanoparticles towards citric acid integrated with computational approach in food and biological media - Huma Ajab; Ali Turab Jafry; Hasnain Sajid; Matthew A. Addicoat; Khurshid Ayub; Muhammad Zia Ul Haq (Food Chemistry, 2024)

Development of stress-induced fracture patterns and accessing reservoir potential of the exposed formations of Panoba Anticline - Tariq Khan; Sohail Wahid; Zahid Rahman; Syed Ali Turab (Carbonates and Evaporites, 2024)

Comparative analysis of the equilibrium, kinetics, and characterization of the mechanism of rapid adsorption of Congo red on nano-biosorbents based on agricultural waste in industrial effluents - Huma Ajab; Durre Nayab; Abdul Mannan; Amir Waseem; Ali Turab Jafry; Asim Yaqub (Journal of Environmental Management, 2024)

Emerging technology effects on combined agricultural and eco-vermicompost - Syed Turab Raza; Adugna Feyissa; Rong Li; Eldon R. Rene; Zulfiqar Ali; Hassan Iqbal; Zulfiqar Ali Sahito; Zhe Chen (Journal of Environmental Management, 2024)

Kahi mélange complex in Kurram and Waziristan, NW Pakistan: An integrated approach for tectonic implications to India–Afghan suturing - Hikmat Salam; Syed Ali Turab; Asghar Ali; M. Qasim Jan; Norasiah Sulaiman; Mohd Basril Iswadi Basori (Gondwana Research, 2024)

Metamorphism of Ladakh Island Arc terrain in the Himalayan region: implications from sulfide geochemistry and petrography - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Tao Wu; Zaheen Ullah; Syed Ali Turab; Tehseen Zafar; Zahid Hussain; Izhar Sadiq; Mubasir Ali (Arabian Journal of Geosciences, 2023)

Impacts of vermicompost application on crop yield, ammonia volatilization and greenhouse gases emission on upland in Southwest China - Syed Turab Raza; Bo Zhu; Zhiyuan Yao; Jianping Wu; Zhe Chen; Zulfiqar Ali; Jia Liang Tang (Science of The Total Environment, 2023)

A two phase escarpment evolution of the Red Sea margin of southwestern Saudi Arabia. Insights from low-temperature apatite thermochronology - Syed Ali Turab; Kurt Stüwe; Finlay M. Stuart; Nathan Cogne; David M. Chew; Jörg Robl (Earth and Planetary Science Letters, 2023)

Comparison of pixel, sub-pixel and object-based image analysis techniques for co-seismic landslides detection in seismically active area in Lesser Himalaya, Pakistan - Sumbal Bahar Saba; Muhammad Ali; Syed Ali Turab; Muhammad Waseem; Shah Faisal (Natural Hazards, 2023)

Radon concentration in drinking water and soil after the September 24, 2019, Mw 5.8 earthquake, Mirpur, Azad Jammu, and Kashmir: an evaluation for potential risk - Said Muhammad; Rizwan Ullah; Syed Ali Turab; Muhammad Younis Khan; Nimat Ullah Khattak; Muhammad Asif Khan (Environmental Science and Pollution Research, 2020)